Ultrastructural analysis of throat dermal tissue and chromatophore components in the threespine stickleback (Gasterosteus aculeatus) - Anderson,Christopher M.; Fink,Thomas; McKinnon,Jeffrey S. (PeerJ, 2023)
The threespine stickleback (Gasterosteus aculeatus) is an important model for studying the evolution of nuptial coloration, but histological analyses of color are largely lacking. Previous analyses of one nuptial coloration trait, orange-red coloration along the body, have indicated carotenoids are the main pigment producing this color. In addition, recent gene expression studies found variation in the correlates of throat coloration between the sexes and between populations, raising the possibility of variation in the mechanisms underlying superficially similar coloration. We used transmission electron microscopy (TEM) to investigate the histological correlates of color in the throat dermal tissue of threespine stickleback from Western North America, within and between sexes, populations, and ecotypes. Ultrastructural analysis revealed carotenoid-containing erythrophores to be the main chromatophore component associated with orange-red coloration in both males and females across populations. In individuals where some darkening of the throat tissue was present, with no obvious orange-red coloration, erythrophores were not detected. Melanophore presence was more population-specific in expression, including being the only chromatophore component detected in a population of darker fish. We found no dermal chromatophore units within colorless throat tissue. This work confirms the importance of carotenoids and the erythrophore in producing orange-red coloration across sexes, as well as melanin within the melanophore in producing darkened coloration, but does not reveal broad histological differences among populations with similar coloration.
Keywords: Threespine stickleback; Gasterosteus aculeatus; Dermal chromatophore; Animal coloration; Histology; Ultrastructure